Efficacy of Intravenous Thrombolysis Combined with Mechanical Stent Interventional Thrombectomy on Acute Ischemic Stroke: intravenous thrombolysis combined with mechanical stent interventional thrombectomy in acute ischemic stroke - Huang, Jun; Zhang, Ming; Nie, Qingbin; Zhang, Xinye; He, Xin; Yang, Yufeng; Mao, Gengsheng (Journal of Medical Biochemistry, 2022)
Background: To investigate the efficacy and safety of intravenous thrombolysis combined with mechanical stent interventional thrombectomy in the treatment of acute ischemic stroke.Methods: A retrospective analysis was carried out for clinical data of 118 patients with acute ischemic stroke admitted to our hospital from January 2017 to March 2018. The patients enrolled were divided into two groups according to different therapies, with 59 cases in each group. Patients in control group were administered with recombinant tissue plasminogen activator (rt-PA) intravenous thrombolysis on the basis of routine symptomatic treatment, while those in thrombectomy group underwent mechanical stent interventional thrombectomy based on rt-PA intravenous thrombolysis. The vascular recanalization rate and clinical efficacy after treatment were compared between the two groups. National Institutes of Health Stroke Scale (NIHSS) was used to identify the degree of neurological impairment in all patients before and after treatment, and Barthel Index was used to assess their activity of daily living. Moreover, the changes in the levels of T-lymphocyte subpopulation in peripheral blood and immuno-inflammatory factors before and after treatment were compared, and prognosis of patients and incidence of adverse reactions were recorded.  Results: Clinical efficacy of all the patients was assessed at 3 months after treatment. The response rate was 93.2% (54/59) and 76.3% (45/59), respectively, in thrombectomy group and control group. It can be seen that the response rate in thrombectomy group was significantly better than that in control group (P=0.024). In the two groups, hemorrhage of digestive tract occurred in 3 cases and 2 cases, and skin and mucosal ecchymosis in 4 cases and 2 cases, respectively, which were all improved after symptomatic treatment. The NIHSS sore and modified Rankin scale (mRS) score after treatment were significantly lower than those before treatment, while the Barthel Index after treatment was distinctly higher than that before treatment (P0.05). Levels of cluster of differentiation 3 (CD3)+, CD3+CD4+, CD4+/CD8+ and natural killer (NK) cells in peripheral blood at 6 months after treatment evidently rose compared with those before treatment (P
Keywords: thrombolysis; mechanical thrombectomy; acute ischemic stroke; efficacy